Effectuation of biogas based hybrid energy system for cost-effective decentralized application in small rural community. (15th July 2020) - Pal, Ankit; Bhattacharjee, Subhadeep
Abstract: Decentralized applications of the renewable energy system (RES) have become extremely popular in rural areas for its pre-eminence over extravagant grid extension. The present study proposes a hybrid renewable energy system (HRES) for a small rural community at Patharpratima island, Sundarbans, India. The abundance of solar energy and cow excrement necessitate the study area fit for an HRES based on PV and biogas plant (BP). The present work introduces a detail biogas resource assessment considering monthly variation in gas production and satisfies an extensive dynamic electricity demand by the proposed HRES. The component sizes of the system have been optimized using particle swarm optimization (PSO) to reduce the total net present value (TNPV). For more practical realization, the typical meteorological year (TMY) data have been used which legitimately estimate the output of the HRES. Furthermore, a system control strategy has been designed to impose the proper operating sequence on the HRES components and to ensure zero loss of power supply probability (LPSP). The suggested model levies a cost of energy (COE) ₹ 9.22/kWh which is found to be very economic than alike systems. Highlights: HRES consists of Biogas, PV, and ESS has been designed for a small rural community. Resource estimation for PV, Biogas seeing effect of temperature on gas production. A Highly dynamic load demand has been fulfilled by the HRES with zero LPSP. The TNPV has been minimized through optimal sizing of the HRES components using PSO.